Kontaminasi Mikroba Patogen pada Produk Ikan Asin Tradisional: Kajian Mikrobiologis - Leviona Dhina Safira; Ardi Mustakim (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Traditional salted fish is a widely consumed food product in Indonesia due to its high shelf life and distinctive flavor. However, the production process, which is generally carried out conventionally and openly, has the potential to cause contamination by pathogenic microbes, which can endanger consumer health. This study aims to identify and analyze the presence of pathogenic microorganisms in traditional salted fish products through a microbiological approach. Salted fish samples were taken from various traditional markets and analyzed using microbial culture methods, biochemical identification, and molecular confirmation for pathogenic bacteria such as Salmonella spp., Vibrio spp., Escherichia coli, and Staphylococcus aureus. The results showed that most contained pathogenic bacteria exceeding the threshold set by SNI and BPOM, indicating weak sanitation and hygiene control in the processing process. These findings emphasize the importance of implementing hygiene standards and quality control in the home industry of salted fish processing. Furthermore, environmental factors such as sea air quality, drying methods, the use of unclean containers, and minimal knowledge of business actors regarding hygiene practices are the main causes of contamination. In some locations, salted fish is dried directly on the ground or on unsterilized surfaces, increasing the risk of exposure to dust, insects, and microorganisms. The study also found that labeling and date information were not available on most products, making it difficult for consumers to assess their safety. As a preventative measure, educating producers and providing training on Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) is crucial. Collaboration between the Health Office, the Food and Drug Monitoring Agency (BPOM), and local governments is also recommended to conduct regular inspections and provide food safety certification facilities for small businesses.